2017
DOI: 10.1111/imj.13542
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and risk factors of colorectal adenoma in patients with early gastric cancer

Abstract: The prevalence of a coexisting advanced CRN was higher in EGC patients. The study shows colonoscopy plays an important role with respect to the detection of synchronous advanced CRN in patients with EGC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Moreover, colonoscopy might be considered for patients with benign GN[ 12 - 14 ]. However, both Chung et al [ 16 ] and Koh et al [ 18 ] revealed that the prevalence of CRN was not significantly different between patients with and without GN. Based on the above findings, our study was designed to address the current controversy and provide more valuable suggestions for GN patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, colonoscopy might be considered for patients with benign GN[ 12 - 14 ]. However, both Chung et al [ 16 ] and Koh et al [ 18 ] revealed that the prevalence of CRN was not significantly different between patients with and without GN. Based on the above findings, our study was designed to address the current controversy and provide more valuable suggestions for GN patients.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, GN was also reported to have potential predictive value for CRN, especially for advanced CRN[ 11 - 15 ]. However, some other studies demonstrated that colonoscopy surveillance is not recommended for all GN patients[ 16 - 18 ]. Therefore, this study sought to investigate whether it is necessary for GN patients to receive colonoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Among the 125 participants who had a prior gastric/small intestinal surgery in this study, 123 underwent gastrectomy mainly due to gastric cancer. Importantly, the incidence of colonic neoplastic lesions in the patients with gastric cancer is higher than that in the general population 171819. Therefore, high-quality colonoscopy is mandatory for these patients.…”
Section: Discussionmentioning
confidence: 99%